Canadian Stroke Best Practice Recommendations: Virtual Stroke Rehabilitation Interim Consensus Statement 2022. (29th November 2022) - Salbach, Nancy M.; Mountain, Anita; Lindsay, M. Patrice; Blacquiere, Dylan; McGuff, Rebecca; Foley, Norine; Corriveau, Hélène; Fung, Joyce; Gierman, Natalie; Inness, Elizabeth; Linkewich, Elizabeth; O'Connell, Colleen; et al.
Abstract: The seventh edition of the Canadian Stroke Best Practice Recommendations for Rehabilitation and Recovery following Stroke includes a new section devoted to the provision of virtual stroke rehabilitation. This consensus statement uses Grading of Recommendations, Assessment, Development and Evaluations methodology and Appraisal of Guidelines for Research & Evaluation II principles. A literature search was conducted using PubMed, Embase, and Cochrane databases. An expert writing group reviewed all evidence and developed recommendations, as well as consensus-based clinical considerations where evidence was insufficient for a recommendation. All recommendations underwent internal and external review. These recommendations apply to hospital, ambulatory care, and community-based settings where virtual stroke rehabilitation is provided. This guidance is relevant to health professionals, people living with stroke, healthcare administrators, and funders. Recommendations address issues of access, eligibility, consent and privacy, technology and planning, training and competency (for healthcare providers, patients and their families), assessment, service delivery, and evaluation. Virtual stroke rehabilitation has been shown to safely and effectively increase access to rehabilitation therapies and care providers, and uptake of these recommendations should be a priority in rehabilitation settings. They are key drivers of access to high-quality evidence-based stroke care regardless of geographical location and personal circumstances in Canada.